2019
DOI: 10.7150/ijms.27595
|View full text |Cite
|
Sign up to set email alerts
|

MEOX1 Promotes Tumor Progression and Predicts Poor Prognosis in Human Non-Small-Cell Lung Cancer

Abstract: Background: MEOX1 is a homeobox transcriptional factor, and plays essential roles in regulating somite development. Our previous study indicated that MEOX1 is a critical molecular target in mesenchymal-like cancer cells in PTEN-deficient Trastuzumab resistant breast cancer. Despite the potential implication of MEOX1 for the cancer progression, no previous studies examined its level and clinical significance in lung cancer tissues. In this study, we aimed to detect the MEOX1 expression and correlate its level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
0
17
3
Order By: Relevance
“…CCR9 associated with T lymphocyte development when bound to its specific ligand, and is highly expressed in variety of cancers [53]. MEOX1 plays key role in regulating somite development, which associated with cancer progression [54]. ADGRE5 was closely related with tumor cell adhesion, migration, angiogenesis, and apoptosis [55].…”
Section: Resultsmentioning
confidence: 99%
“…CCR9 associated with T lymphocyte development when bound to its specific ligand, and is highly expressed in variety of cancers [53]. MEOX1 plays key role in regulating somite development, which associated with cancer progression [54]. ADGRE5 was closely related with tumor cell adhesion, migration, angiogenesis, and apoptosis [55].…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional data point to a nuanced role of TIM-3 in GBM. The association between high TIM-3 expression and the downregulation of genes including MEOX1, CAPN6, PRAC1 and CXCL17 in GBM suggests the role of this receptor may not be fully inhibitory, owing to the pro-tumorigenic roles that have been described for these genes [ 44 , 45 , 46 , 47 , 48 ]. TIM-3, instead, appears to be involved in a varied set of immunological responses in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that MEOX1 may be involved in the development of some carcinoma. MEOX1 was over expressed in several cancers than normal tissues, such as prostate cancer, ovarian cancer, non-small-cell lung cancer and breast cancer [7,8,18,19]. Also, MEOX1 is related to signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MEOX1 was evaluated by semiquantitative method [8]. The number of positive cancer cell was scored between 0 to 3 (0, 0%; 1, ≦25%; 2, 26%-50%; 3, ≥ 50%).…”
Section: Immunohistochemistry and Staining Evaluationmentioning
confidence: 99%
See 1 more Smart Citation